Financial ratios and indicators that determine return on equity - Kharatyan, Davit (2017)
This study aims to investigate factors that affect return on equity (ROE). Firms with higher ROE typically have competitive advantages over their competitors which translates into superior returns for investors. Therefore, it seems imperative to study the drivers of ROE, particularly financial ratios/indicators that may have considerable impact on it. The analysis is done on a sample of 90 non-financial companies, components of NASDAQ-100 index. The ordinary least squares method is used to find the most impactful drivers of ROE. The extended DuPont model’s components are considered as the primary factors affecting ROE. In addition, other ratios/indicators such as price to earnings, price to book and current are also incorporated. Consequently, the study uses eight ratios/indicators that are believed to have impact on ROE. According to our findings, the most relevant ratios that determine ROE are tax burden, interest burden, operating margin, asset turnover and Financial leverage.